Dodonaea viscosa var angustifolia derived 5, 6, 8-trihydroxy-7, 4′ dimethoxy flavone inhibits ergosterol synthesis and the production of hyphae and biofilm in Candida albicans. (15th September 2020) - Patel, Mrudula; Srivastava, Vartika; Ahmad, Aijaz
Abstract: Ethnopharmacological relevance: Candida albicans is developing resistance to existing drugs increasing morbidity and mortality, which elevates an immediate need to explore new antifungal agents. Phytochemicals are an excellent source of therapeutic agents. We previously reported the antifungal activity of the crude extract of Dodonaea viscosa var. angustifolia Jacq. (DVA) from which a beneficial compound flavone: 5, 6, 8-trihydroxy-7, 4′ dimethoxy flavone ( 5, 6, 8-trihydroxy-7-methoxy-2-(4-methoxyphenyl)-4 H -chromen-4-one) abbreviated as TMMC, was extracted. Aim of the study: The present study evaluated the effect of a TMMC subfraction on biofilms, membrane stability, ergosterol biosynthesis and germ tube (GT) formation in Candida albicans . Materials and methods: Extracts were prepared and fractionated to obtain purified TMMC. Minimum inhibitory concentrations of TMMC were obtained and subinhibitory concentrations were selected for further studies. Confocal laser scanning microscopy (CLSM) was performed to assess the effect of TMMC on membrane permeability and sterol deposition using propidium iodide (PI) and filipin stains, respectively. Results: Minimum inhibitory concentrations (MIC) and Minimum Fungicidal concentrations (MFC) of TMMC were 0.39 mg/mL and 1.56 mg/mL, respectively. TMMC inhibited biofilm formation and damaged mature biofilms at 0.39 mg/mL and 1.56 mg/mL, respectively. CLSM further confirmed the disruption and architectural changes in biofilms following treatment with TMMC. TMMC also inhibited GT formation and ergosterol biosynthesis in a concentration dependent manner, which was further confirmed by varying sterol distribution and membrane disruption in treated and untreated cells. Conclusions: With the multiple targets at different concentrations, TMMC warrants its potential use as antifungal drug against C. albicans . However further studies using animal models and more mechanistic approaches will be required . Graphical abstract: Image 1 Highlights: Dodonaea viscosa var. angustifolia derived flavone inhibits hyphae in C. albicans . It also inhibits biofilm formation and ergosterol synthesis. The beneficial effects are due to the damage to the C. albicans cell membrane. This flavone has potential to be developed into an antifungal agent.